Students Motivation and Understanding of Football Using Android Media - Bambang Gatot Sugiarto (STAI Hubbulwathan Duri, 2021)
In this pandemic period, a teacher must use effective media in the learning process to increase student understanding and motivation. This study aimed to see differences in student motivation and understanding in learning football material before and after using android media. This research is quantitative research with a pre and post-test design group. The population in this study was the eighth class of VIII SMPN 1 Cimahi, Cimahi Regency, the academic year 2020-2021 in August. The sample in this study was in the eighth class of SMPN 1 Cimahi. Statistical analysis used a parametric test if it fulfilled the classical assumptions. The results showed increased student motivation and understanding of football material before and after implementing learning using Android media. Through these results, the teacher can use Android to learn, especially during a pandemic like now.